Yellow Pumpkin (Cucurbita maxima D.) Extract As Anti-Hypercholesterolemia - Istianatus Sunnah; Erna Kustiyaningsih; Dian Oktianti (Universitas Muhammadiyah Yogyakarta, 2021)
Hyperlipidemia is a risk factor for various diseases, which is still a big problem in Indonesia. Yellow pumpkin (Cucurbita maxima D.) is a plant containing flavonoids and terpenoids, which can be used as an anti-hypercholesterolemic agent. This study aims to analyze the activity and dosage of yellow pumpkin extract, which can be used as an anti-hypercholesterolemic agent to reduce total cholesterol levels comparable to simvastatin by 1.8mg/kg BW/day. This research is pure experimental research with a pre and post-test group design approach. The number of samples was 25 male Wistar rats induced by high-fat feed, quail egg yolk: pork oil (2:1) by 5 ml/200 gramBW/day for 7 days. The extract dosage range was 200, 400, 600 mg/kg BW/ day for 7 days. Data were analyzed using One Way ANOVA. The results showed that the administration of yellow pumpkin extract could reduce rats' total blood cholesterol levels with a dose of 600 mg/kg BW/day, comparable to simvastatin 1.8 mg/kg BW/day. The secondary metabolites of the extract were flavonoids and terpenoids. Extract of yellow pumpkin (Cucurbita maxima D.) could reduce total blood cholesterol levels of rats. The dose of 600 mg/kg BW/day could reduce blood cholesterol levels in rats comparable to simvastatin 1.8 mg/kg BW/ day.